Designing of Comic Strip as Learning Media in Future Tense Material - Catur Sunu Wijayanto; Fitria Iswari; Dian Handayani (Cultural Syndrome, 2020)
In Indonesia, English is one of language which is learnt from elementary school University level. College students from Visual communication design program in first semester will get future tense material in English 1. In future tenses there 2 formulas which are used based on the functional of the sentence, and it is difficult for student in differentiating the formulas, Media has important role in teaching learning process.  Comic strip is familiar for milenilal. Based on the background writer decide to design a comic strip as learning media. The designing of comic strip is aim to give new or alternative media in teaching learning process. This comic strip covers future tense material that includes “to be going to” and “will” form. This research used qualitative method. The results of this research is designing of a comic strip in 8 panels that is written in English and covered future tense material which give ilutration how the two formulas of future tenses are used.  The typography is comic sans MS, the main characters are three girls of Senior High School student. Comic strip is made in tradiotional/ manual process by drawing use pencil then through digitally process for the finishing. The colour of the comic strip uses calm colours and are dominated grey according to senior high school uniform colour, in order to make the reader feel the comfortable. The conclusion shows comic strip could be an alternative media in learning process.